Nilai-Nilai Pendidikan Islam dalam Novel “Hafalan Shalat Delisa” Karya Tere Liye - Ardiagarini, Esti; Daripah, Udung Hari (Jurnal Penelitian Pendidikan Islam, 2017)
This article examines the values of Islamic education in Tere Liye's novel “Hafalan Prayer Delisa”. The importance of studying the values of education in literary works because the literary work is more desirable students compared with scientific work. Thus, the appeal of literary works is greater than that of scientific work, so the study of the values of Islamic education in literary works is considered important. This novel contains religious values, education and morals, so worthy of being used as learning.